The actual fossil documentation for the theorie of anthropogenesis - Stęślicka, Wanda (Anthropological Review, 1976)
The author presents a review of the fossil higher Primates and discusses their taxonomic position. Palacontological evidence leads to the conclusion that the process of hominisation must be referred to the Pliocene.